2013
DOI: 10.1177/0143034313479697
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying among youth: A comprehensive review of current international research and its implications and application to policy and practice

Abstract: Cyberbullying research is rapidly expanding with many studies being published from around the world in the past five or six years. In this article we review the current international literature published in English, with particular attention to the following themes: The relationship of cyberbullying to the more traditional face-to-face bullying, including differences and similarities; the impacts of cyberbullying on victims, bullies, schools, families, and communities; coping strategies for victims, schools, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
183
0
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(213 citation statements)
references
References 97 publications
8
183
0
22
Order By: Relevance
“…These findings corroborate with the findings from previous studies (Arumugam, Ruuhina & Paramjit 2014;Cassidy, Faucher & Jackson 2013). These students are also less negatively affected by SN than the students in Thang et al's (2016) study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings corroborate with the findings from previous studies (Arumugam, Ruuhina & Paramjit 2014;Cassidy, Faucher & Jackson 2013). These students are also less negatively affected by SN than the students in Thang et al's (2016) study.…”
Section: Discussionsupporting
confidence: 92%
“…Children and adolescents are particularly vulnerable to such risks as they are less aware of the necessity for self-regulation and are more susceptible to cyberbullying, privacy issues and sexting (O'Keeffe, Clarke-Pearson & Council on Communications and Media Executive Commitee 2011;Cassidy, Faucher & Jackson 2013). These issues have caused concerns and led to increased efforts to comprehend the attitudes and behaviours of children and teenagers toward SN.…”
Section: Rangkaian Sosial (Rs) Membolehkan Individu Berkomunikasi Antmentioning
confidence: 99%
“…This could be further explained once the type of bullying is considered, although not specifically examined in the current analysis. Previous studies reported that females are more likely than males to be victims of cyberbullying which in turn has been linked with worse mental health outcomes such as suicidal ideation (Bannink, Broeren, van de Looij-Jansen, de Waart, & Raat, 2014;Cassidy, Faucher, & Jackson, 2013). The literature indicates that when being faced with adversities such as negative peer events, females experience more interpersonal stress and report more distress as compared to males (Rose & Rudolph, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Negative consequences of cyberbullying range from minor to lethal depending on the content, frequency, intensity, anonymity, type of technology used and medium where cyberbullying occurs. Cassisdy, Faucher and Jackson (2013) noted that many of the negative effects stemming from cyberbullying overlap with the consequences of traditional bullying such as depression, poor selfesteem, anxiety, suicidal ideation and some sort of psychosomatic problems.…”
Section: Introductionmentioning
confidence: 99%